Tuning the size of a redox-active tetrathiafulvalene-based self-assembled ring - Bivaud, Sébastien; Goeb, Sébastien; Croué, Vincent; Allain, Magali; Pop, Flavia; Sallé, Marc (Beilstein Journal of Organic Chemistry, 2015)
The synthesis of a new Pd coordination-driven self-assembled ring M6L3 constructed from a concave tetrapyridyl π-extended tetrathiafulvalene ligand (exTTF) is described. The same ligand is also able to self-assemble in a M4L2 mode as previously described. Herein, we demonstrate that the bulkiness of the ancillary groups in the Pd complex allows for modulating the size and the shape of the resulting discrete self-assembly, which therefore incorporate two (M4L2) or three (M6L3) electroactive exTTF sidewalls.
Keywords: coordination; metal-driven; redox; self-assembly; tetrathiafulvalene

(untitled) - Amouri, H.; Desmarets, C.; Moussa, J. (Chem. Rev., 2012)

(untitled) - MacGillivray, L. R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Chakrabarty, R.; Mukherjee, P. S.; Stang, P. J. (Chem. Rev., 2011)

(untitled) - Inokuma, Y.; Kawano, M.; Fujita, M. (Nat. Chem., 2011)

(untitled) - Jin, P.; Dalgarno, S. J.; Atwood, J. L. (Coord. Chem. Rev., 2010)

(untitled) - De, S.; Mahata, K.; Schmittel, M. (Chem. Soc. Rev., 2010)

(untitled) - Therrien, B. (Eur. J. Inorg. Chem., 2009)

(untitled) - Northrop, B. H.; Zheng, Y.-R.; Chi, K.-W.; Stang, P. J. (Acc. Chem. Res., 2009)

(untitled) - Stang, P. J. (J. Org. Chem., 2009)

(untitled) - Yoshizawa, M.; Klosterman, J. K.; Fujita, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Han, Y.-F.; Jia, W.-G.; Yu, W.-B.; Jin, G.-X. (Chem. Soc. Rev., 2009)

(untitled) - Northrop, B. H.; Chercka, D.; Stang, P. J. (Tetrahedron, 2008)

(untitled) - Northrop, B. H.; Yang, H.-B.; Stang, P. J. (Chem. Commun., 2008)

(untitled) - Cooke, M. W.; Chartrand, D.; Hanan, G. S. (Coord. Chem. Rev., 2008)

(untitled) - Dalgarno, S. J.; Power, N. P.; Atwood, J. L. (Coord. Chem. Rev., 2008)

(untitled) - Zangrando, E.; Casanova, M.; Alessio, E. (Chem. Rev., 2008)

(untitled) - Mukherjee, S.; Mukherjee, P. S. (Chem. Commun., 2014)

(untitled) - Mishra, A.; Kang, S. C.; Chi, K.-W. (Eur. J. Inorg. Chem., 2013)

(untitled) - Cook, T. R.; Vajpayee, V.; Lee, M. H.; Stang, P. J.; Chi, K.-W. (Acc. Chem. Res., 2013)

(untitled) - Croué, V.; Goeb, S.; Sallé, M. (Chem. Commun., 2015)

(untitled) - Uehara, K.; Kasai, K.; Mizuno, N. (Inorg. Chem., 2010)

(untitled) - Ferrer, M.; Pedrosa, A.; Rodriguez, L.; Rossell, O.; Vilaseca, M. (Inorg. Chem., 2010)

(untitled) - Ghosh, S.; Mukherjee, P. S. (Inorg. Chem., 2009)

(untitled) - Sun, Q.-F.; Wong, K. M.-C.; Liu, L.-X.; Huang, H.-P.; Yu, S.-Y.; Yam, V. W.-W.; Li, Y.-Z.; Pan, Y.-J.; Yu, K.-C. (Inorg. Chem., 2008)

(untitled) - Yamamoto, T.; Arif, A. M.; Stang, P. J. (J. Am. Chem. Soc., 2003)

(untitled) - Fujita, M.; Sasaki, O.; Mitsuhashi, T.; Fujita, T.; Yazaki, J.; Yamaguchi, K.; Ogura, K. (Chem. Commun., 1996)

(untitled) - Maeda, H.; Akuta, R.; Bando, Y.; Takaishi, K.; Uchiyama, M.; Muranaka, A.; Tohnai, N.; Seki, S. (Chem. – Eur. J., 2013)

(untitled) - Schweiger, M.; Seidel, S. R.; Arif, A. M.; Stang, P. J. (Inorg. Chem., 2002)

(untitled) - Goeb, S.; Bivaud, S.; Dron, P. I.; Balandier, J.-Y.; Chas, M.; Sallé, M. (Chem. Commun., 2012)

(untitled) - Holló-Sitkei, E.; Tárkányi, G.; Párkányi, L.; Megyes, T.; Besenyei, G. (Eur. J. Inorg. Chem., 2008)

(untitled) - Weilandt, T.; Troff, R. W.; Saxell, H.; Rissanen, K.; Schalley, C. A. (Inorg. Chem., 2008)

(untitled) - Ferrer, M.; Gutiérrez, A.; Mounir, M.; Rossell, O.; Ruiz, E.; Rang, A.; Engeser, M. (Inorg. Chem., 2007)

(untitled) - Ferrer, M.; Mounir, M.; Rossell, O.; Ruiz, E.; Maestro, M. A. (Inorg. Chem., 2003)

(untitled) - Fang, Y.; Murase, T.; Sato, S.; Fujita, M. (J. Am. Chem. Soc., 2013)

(untitled) - Balandier, J.-Y.; Chas, M.; Goeb, S.; Dron, P. I.; Rondeau, D.; Belyasmine, A.; Gallego, N.; Sallé, M. (New J. Chem., 2011)

(untitled) - Goeb, S.; Bivaud, S.; Croué, V.; Vajpayee, V.; Allain, M.; Sallé, M. (Materials, 2014)

(untitled) - Vajpayee, V.; Bivaud, S.; Goeb, S.; Croué, V.; Allain, M.; Popp, B. V.; Garci, A.; Therrien, B.; Sallé, M. (Organometallics, 2014)

(untitled) - Bivaud, S.; Goeb, S.; Balandier, J. Y.; Chas, M.; Allain, M.; Sallé, M. (Eur. J. Inorg. Chem., 2014)

(untitled) - Bivaud, S.; Goeb, S.; Croué, V.; Dron, P. I.; Allain, M.; Sallé, M. (J. Am. Chem. Soc., 2013)

(untitled) - Bivaud, S.; Balandier, J.-Y.; Chas, M.; Allain, M.; Goeb, S.; Sallé, M. (J. Am. Chem. Soc., 2012)

(untitled) - Cohen, Y.; Avram, L.; Frish, L. (Angew. Chem., Int. Ed., 2005)

(untitled) - Schneebeli, S. T.; Frasconi, M.; Liu, Z.; Wu, Y.; Gardner, D. M.; Strutt, N. L.; Cheng, C.; Carmieli, R.; Wasielewski, M. R.; Stoddart, J. F. (Angew. Chem., Int. Ed., 2013)